CHILDHOOD AND INTERNATIONAL RELATIONS: REFLECTIONS ON THE EXPERIENCE OF SUBALTERNITY AND INVISIBLE AGENCY OF CHILDREN IN DISCIPLINE - Luara Dias dos Santos; Joana D'arc Moreira; Marrielle Maia (Revista Tempo do Mundo)
This article examines the role of children as subaltern subjects in International Relations, addressing how their voice and participation are often neglected in global decision making rocesses. Despite being directly impacted by wars, migration crises and climate change, children have their experiences and opinions mediated or silenced by adult-centric power structures. From a postcolonial perspective, we discuss how subalternity theory can be applied to understand the marginalization of children and explore concrete examples in which their political agency has been ignored or undervalued. We conclude with the need to restructure international bodies so that children are recognized as legitimate actors, with the right to voice and active participation.To this end, the article first examines the place that children occupy in debates within the discipline of international relations, questioning how and why the discipline has neglected children and childhood. It then discusses the issue of agency in international relations and how this correlates with children and childhood. Finally, uses Spivak’s concept of subalternity to identify the place of children in the discipline.